Library of essays in global governance - Kirton, John J.; Madunic, Jelena (The library of essays in global governance, 2009)
A collection of five volumes that looks at issues related to the global management of health, the rules of international law, global trade agreements and policy, international economics and finance and international organisations. It is suitable for scholars in international relations and political science.